Development of Spatial and Land Planning Applications in North Sumatra Province (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The development of information technology drives digital transformation in the implementation of spatial planning, particularly in the management of spatial data and the provision of information to the public. The management of Regional Spatial Planning (RTRW) data that is still scattered across various documents makes the process of information retrieval and public services less effective. This study aims to develop a WebGIS-based application of the North Sumatra Spatial Planning and Land Information System (SIPINTAR SUMUT) as a medium for integrating spatial and non-spatial data to support the planning, utilization, and control of spatial utilization in North Sumatra Province. The study uses the Design Science Research (DSR) method which includes the stages of problem identification, goal determination, system design and development, demonstration, evaluation, and communication of results. The research data consists of base maps, thematic maps, plan maps, RTRW documents, and other supporting data integrated into the WebGIS-based system. The results show that SIPINTAR SUMUT has been successfully developed with main features such as a homepage, interactive maps, information on spatial structure, spatial patterns, forest areas, marine zones, user authentication, and a public complaint page that supports public participation in monitoring spatial utilization. The application's implementation can improve ease of access to spatial planning information, accelerate spatial data retrieval, support transparency in public services, and increase the efficiency of spatial planning data management within the North Sumatra Provincial Government. Therefore, SIPINTAR SUMUT can serve as a model for implementing WebGIS-based spatial planning digitization, supporting effective, transparent, and participatory governance.